Transient, Recurrent Central Nervous System Clinical Manifestations of X-Linked Charcot-Marie-Tooth Disease Presenting with Very Long Latency Periods between Episodes: Is Prolonged Sun Exposure a Provoking Factor? - Andria Tziakouri; Konstantinos Natsiopoulos; Kleopas A. Kleopa; Costas Michaelides (Case Reports in Neurological Medicine)
Charcot-Marie-Tooth disease is one of the most common inherited neurological disorders affecting the peripheral nervous system. The common clinical manifestations of the disease are distal muscle weakness and atrophy, often associated with a characteristic steppage gait and foot deformities. Transient acute and recurrent or chronic central nervous system manifestations, predominantly, dysarthria, dysphagia, motor weakness, and ataxia, have been recognized as a feature of the X-linked type 1 of CMT (CMTX1). The CNS symptoms occur typically in young age and often precede the clinical manifestation of the polyneuropathy. Several predisposing factors such as exercise, fever, and returning from areas of high altitude have been described as triggers of the CNS symptoms; however, in many cases, a substantial cause remains undetermined. In this report, we describe a patient with three attacks of transient CNS deficits at the ages of 11, 21, and 38 years, respectively, which were also accompanied by transient white matter abnormalities on MRI. Two of the attacks occurred after prolonged exposure to sunlight. In our knowledge, this is the first documented case with such long latency periods between CNS attacks as well as the only report describing intense sun exposure as a possible provoking factor.